Discovery of Genes that Modulate Flavivirus Replication in an Interferon-Dependent Manner. Issue 6 (30th March 2022) - Lesage, Sarah; Chazal, Maxime; Beauclair, Guillaume; Batalie, Damien; Cerboni, Silvia; Couderc, Elodie; Lescure, Aurianne; Del Nery, Elaine; Tangy, Frédéric; Martin, Annette; Manel, Nicolas; Jouvenet, Nolwenn
Graphical abstract: Highlights: Numerous genes that contribute to the antiviral state remain to be identified. A screen recovered host proteins that modulate ZIKV replication in IFN-stimulated cells. APOL3 acts as a proviral factor for ZIKV and several other RNA viruses. MTA2 is as a potent flavivirus-specific antiviral gene. Our study opens perspectives to target weakness points in the life cycle of viruses. Abstract: Establishment of the interferon (IFN)-mediated antiviral state provides a crucial initial line of defense against viral infection. Numerous genes that contribute to this antiviral state remain to be identified. Using a loss-of-function strategy, we screened an original library of 1156 siRNAs targeting 386 individual curated human genes in stimulated microglial cells infected with Zika virus (ZIKV), an emerging RNA virus that belongs to the flavivirus genus. The screen recovered twenty-one potential host proteins that modulate ZIKV replication in an IFN-dependent manner, including the previously known IFITM3 and LY6E. Further characterization contributed to delineate the spectrum of action of these genes towards other pathogenic RNA viruses, including Hepatitis C virus and SARS-CoV-2. Our data revealed that APOL3 acts as a proviral factor for ZIKV and several other related and unrelated RNA viruses. In addition, we showed that MTA2, a chromatin remodeling factor, possesses potent flavivirus-specific antiviral functions induced by IFN. Our work identified previously unrecognized genes that modulate the replication of RNA viruses in an IFN-dependent manner, opening new perspectives to target weakness points in the life cycle of these viruses.